Association between Sarcopenia and Renal Function in Patients with Diabetes: A Systematic Review and Meta-Analysis. (18th November 2019) - Ida, Satoshi; Kaneko, Ryutaro; Imataka, Kanako; Murata, Kazuya
Abstract : Previous studies involving patients with diabetes have indicated that sarcopenia is related to renal function. The objective of the present study was to investigate the association between sarcopenia and urinary albumin level, urinary protein level, and estimated glomerular filtration rate (eGFR) in patients with diabetes. A meta-analysis of observational studies was conducted. A literature search was performed using MEDLINE, Cochrane Controlled Trials Registry, and ClinicalTrials.gov. Data were extracted from studies investigating the association between sarcopenia and urinary albumin level, urinary protein level, and eGFR and by calculating odds ratio (OR) and 95% confidence intervals (CIs). Statistical analysis was performed using a random-effects model to calculate pooled OR and 95% CI. Six studies (2662 patients) that met the criteria were included in the meta-analysis. Sarcopenia was significantly associated with urinary albumin level with a pooled OR of 2.11 (95% CI, 1.55–2.88; P < 0.001 ). The pooled ORs of the associations between sarcopenia and urinary protein level and decreased eGFR were 1.82 (95% CI, 1.13–2.92; P = 0.01 ) and 3.75 (95% CI, 1.24–11.41), respectively. Sarcopenia was significantly associated with urinary albumin level, urinary protein level, and decreased eGFR. However, further investigations are needed, including meta-analyses with a larger number of studies.